Stem Cell-Based Therapy for Lung Disease 2019
DOI: 10.1007/978-3-030-29403-8_12
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficiency of Addressing ARDS Using Stem Cell Therapies in Clinical Trials

Abstract: Acute Respiratory Distress Syndrome (ARDS) is a complex and debilitating disease of the lungs, which continues to have a high mortality rate and huge disease burden on patients. Incidence is rising, possibly due to greater awareness leading to more diagnoses rather than a change in the underlying rate. It arises from multiple etiologies, though pathogenic infection, termed pneumonia, is the most prevalent and widely studied. The distinct pathophysiology and rapid evolution of ARDS makes it uniquely challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 184 publications
(203 reference statements)
0
5
0
Order By: Relevance
“…Since 2014 until the COVID-19 pandemic, approximately 30 registered clinical trials have used MSCs for ARDS. Most of these trials have not begun or are currently recruiting patients and lack an update status [25]. From these trials, there are only three published final reports from phase 1-2 studies that focused on safety, tolerability, and feasibility of MSCs for ARDS [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014 until the COVID-19 pandemic, approximately 30 registered clinical trials have used MSCs for ARDS. Most of these trials have not begun or are currently recruiting patients and lack an update status [25]. From these trials, there are only three published final reports from phase 1-2 studies that focused on safety, tolerability, and feasibility of MSCs for ARDS [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This “cytokine storm” is responsible for early sepsis-related multiple organ failure and death [ 3 ]. Mesenchymal stromal cells (MSCs) are a promising therapeutic strategy for the treatment of sepsis due to their reported immunomodulatory properties [ 4 ] and have been shown to have a multimodal mechanism of action involving cytokine and other factor production, secretion of extracellular vesicles and even cell–cell contact-dependent processes [ 5 , 6 , 7 ]. Previous studies have shown the efficacy of these cells to improve the outcome of sepsis of different aetiologies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been debated that the lung has limited regenerative capacities [ 64 , 74 ]. However, as we have set out above, therapies such as MSC secretome, exosomes and conditioned media can be produced and stored and still maintain their viability prior to administration.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…However, the choice between the two strategies depends on the circumstance at hand. Preclinical trials have demonstrated that autologous cell therapy may not be the best option for chronic lung disease [ 64 ]. It may be challenging to isolate and expand cells from older patients due to their decreased biological activity, or from a patient that is severely ill due to their immune suppression properties and low immunogenicity, and the isolation and expansion of MSCs is a time-consuming process [ 65 ].…”
Section: Introductionmentioning
confidence: 99%